Work stress prevalence among the management staff in an international tobacco company in Malaysia - W.F. Swee; Anza E; Noor Hassim I (Penerbit UKM, 2007)
A cross sectional study on work stress prevalence was carried out among 185 executives and managers in the head quarter of an international tobacco company. The aim of the study was to identify work stress prevalence in this company and work stressors that were associated with stress experienced by the workers. A questionnaire based on the Personal Stress Inventory by O'Donell (1984) was used. Data collected from participants included sociodemography factors, symptoms of stress and work stressors related to organizational policy, organizational structure, organizational process, and work environment. The study showed that the prevalence of stress among executives was 68.1% and managers were 67.9%. There was no significant difference in the level of stress between the executives and the managers in the company. The sociodemographic factors that were significantly associated with stress were salary, number of children and personal factors. The significant stressors in the workplace were lack of job recognition, over focusing on quality of work, heavy workload and long working hours